Students’ Understanding on Spoken Discourse in The Context of English Language Teaching (ELT) at University - Dias Andris Susanto; Masitoh Oktavia; Lina Tri Astuty Beru Sembiring (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2021)
Abstract. This is a case study on students’ understanding towards a subject of discourse analysis at English language education study program at University in Indonesia. The goal of this study is to describe the definitions, the examples, and the applications of spoken discourse analysis on their context of English language teaching (ELT). The writers used qualitative research approach to analyze these data through implementing Atlas.ti8 which is known as the tool of analyzing the field qualitative data. The sample was the students of 7th grade semester consisting 30 people. In collecting the data, we used online direct interview in the classroom and by time they replied the questions on the time using the google form by Microsoft. In analyzing the data, we used atlas.ti.8 online to draw the result of the research as followings; that students’ understanding about the definitions of spoken discourse analysis have some various key terms like; -a research method of spoken language, -knowledge of language, how language used, study of language, and study of the texts. Then, its examples are; they can picturize as; speaking on the phone, conversation, interview, putting markers, turn taking, group of discussion, using advertisement, people interaction, joke, speech, also transferring information. Moreover, its applications are such as; communicating with teachers/parents, interacting with students/people, go to the market, baby crying, ceremony, and communicating with friends. The conclusion is that spoken discourse analysis has been understood by students even though it is not easy to define, giving example and declaring the application in the real context English language teaching. Keywords: students’ understanding, spoken discourse analysis, ELT